Design and Development of an Axial Flow Thresher for Seed Crops - Bansal, N K; Lohan, Shiv Kumar (Journal of Agricultural Engineering, 2009)
An axial flow thresher was designed and developed to maintain the seed quality of major oil seed and pulse crops. Major features of the thresher are minimum injury to seed, higher seed recovery and good seed quality, easy feeding and less fatigue to labour. The cylinder speed and aspirator speed are independent and very convenient to vary as per seed size. It has provision of easy adjustment of concave clearance, sieve clearance and slope of sieves. At optimum combination of cylinder sped and concave clearance at different seed moisture contents to thresh oilseeds and pulse crops, the performance parameters were within acceptable ranges of visible seed damage =2% and threshing efficiency =95% with threshed seed germination percentage of green gram (88%), black gram (90%), soybean (90%), chickpea (90%) and sunflower (86%). The germination percentages were above the minimum seed standards suggested by ISTA, (1999).